2020
DOI: 10.34172/joddd.2020.035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of incorporation of triphala into AH26 sealer on its cytotoxicity at different intervals

Abstract: Background. One of the essential properties of sealers used during endodontic treatment is their biocompatibility. Different materials are added to these sealers to improve their properties, including antibacterial activity. In recent years, there has been an increase in interest in the use of herbal medicines. This study aimed to evaluate the effect of incorporating triphala into AH26 sealer on its cytotoxicity on gingival fibroblasts at different intervals after mixing. Methods. In the present in vitro study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Resin-based sealers like AH26 have been commonly applied in endodontics although, formaldehyde release by these sealers leads to cytotoxicity. Previous studies have shown that the maximum toxicity of this sealer is in the rst 24 hours, and the toxicity of this sealer decreases as the sealer sets (22). Aluminum is one of the elements that is found in high amounts in Endoseal and since the cytotoxicity and toxicity effects of aluminum on animals have been observed, this element can be considered as the cause of cytotoxicity induced by this sealer; The effect of zirconium oxide found in Ceraseal as an opaci er has been proven to induce the proliferation of broblasts and accelerate the reduction of in ammatory reactions, as well as the cytotoxic effects of dental materials containing bismuth have been demonstrated.…”
Section: Discussionmentioning
confidence: 97%
“…Resin-based sealers like AH26 have been commonly applied in endodontics although, formaldehyde release by these sealers leads to cytotoxicity. Previous studies have shown that the maximum toxicity of this sealer is in the rst 24 hours, and the toxicity of this sealer decreases as the sealer sets (22). Aluminum is one of the elements that is found in high amounts in Endoseal and since the cytotoxicity and toxicity effects of aluminum on animals have been observed, this element can be considered as the cause of cytotoxicity induced by this sealer; The effect of zirconium oxide found in Ceraseal as an opaci er has been proven to induce the proliferation of broblasts and accelerate the reduction of in ammatory reactions, as well as the cytotoxic effects of dental materials containing bismuth have been demonstrated.…”
Section: Discussionmentioning
confidence: 97%